Faktor risiko kejadian kusta - Aprizal Aprizal; Lutfan Lazuardi; Hardyanto Soebono (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Risk factors of leprosy in district of LamonganPurposeThis study aimed to know the risk factors of leprosy incidence in Lamongan district including economic status or family income, BCG vaccination, residential density, floor conditions, source of water, contact history, bathing habit using soap and using footwear. MethodsThe research was a case-control study. The subjects were the people who had clinical or laboratory symptoms, leprosy diagnosed and recorded in the health center register. The samples were 170 people, consisting of 85 cases and 85 controls. The data were analysed using chi-square and logistic regression tests, and the amount of the risk was calculated using odds ratio. ResultsThe risk-factors associated with the incidence of leprosy in Lamongan were the economic status or family income (OR=4.3 and p=0.001), BCG vaccination (OR=4.3 and p=0.050), residential density (OR=3.2 and p=0.001), floor conditions (OR=2.8 and p=0.051), source of water (OR=2.1 and p=0.033), contact history (OR=7.8 and p=0.001), bathing habit using soap (OR=3.1 and p=0.022) and using footwear (OR=3.1 and p=0.004). The dominant risk factor was BCG vaccination (OR = 8.1 and p=0.025). ConclusionThere were correlations between leprosy incidence and the economic status or family income, BCG vaccination, residential density, floor conditions, source of water, contact history, bathing habit using soap and using footwear. The dominant risk factor was BCG vaccination.